Influence of Spawning Ground Dynamics on the Long-Term Abundance of Japanese Flying Squid (Todarodes pacificus) Winter Cohort - Liu, Yang; Xia, Xinmei; Tian, Yongjun; Alabia, Irene D.; Ma, Shuyang; Sun, Peng; Saitoh, Sei-Ichi (Frontiers in Marine Science, 2021)
Japanese flying squid (Todarodes pacificus) is one of the most commercially important resources in the Pacific Ocean and its abundance is largely affected by environmental conditions. We examined the influence of environmental factors in potential spawning grounds of the winter cohort, approximated from Japanese and South Korean catch and catch per unit effort (CPUE) data of Japanese flying squid. Annual spawning ground dynamics were constructed using sea surface temperature (SST), submarine elevation and mean Kuroshio axis data from 1979 to 2018. Based on these information, we generated a suite of spawning ground indices including suitability SST-weighted area of potential spawning ground (SSWA), mean values (January–April) of suitable SST (MVSS), and the meridional position (MP) of SST isolines (18–24°C). Comparable interannual-decadal variability patterns were detected between the squid abundance and spawning ground indices, with abrupt shifts around 1990/1991 and in recent decades. In particular, the Pacific Decadal Oscillation is negatively correlated with spawning ground indices, suggesting its role in regulating the environmental dynamics in the area. Further, the gradient forest model underpinned the importance of SSWA, SSWA_Lag1 and MVSS_Lag1 on squid abundance. The CPUE is also shown to be a better abundance index than the annual catch in modeling the species’ response to environmental variability in its spawning grounds. Our findings suggest that it is imperative to pay more and timely attention to the relationship between the abundance of Japanese flying squid and environmental changes, especially under adverse environmental conditions.